Assessment of Rabbit Ovarian Reserve and Folliculogenesis by E-cadherin Plasma Level Estimation (Iraqi Journal of Medical Sciences, 2024)
Background: The primary reproductive organs in females are the ovaries, which produce hormones like estradiol and progestins as well as release mature ova. The ovary is made up of two layers; the outer layer, known as the cortex and the medulla is the inner layer. E-cadherin is a single-span transmembrane glycoprotein with five repetitions and a cytoplasmic domain. It plays a variety of roles, including ensuring tissue integrity and resistance to stretching, cell signaling, regulation of cell proliferation, apoptosis, survival, and carcinogenesis.Objective: To assess E-cadherin level as predicting parameter for ovarian reserve. Methods: Female's rabbits (Oryctolagus cuniculus) of age (10 to more than 108 weeks), weighting 600-3000 grams were randomized into two groups: group A (25 sample, young group), group B (25 sample, old group). All groups' animals prior to euthanasia, blood was collected from the heart for assessment of plasma level of E-cadherin and then euthanized the animals. Specimens of ovaries were placed on standard glass slides for Hematoxylin and Eosin stain for demonstration of the cellular components of the ovary and follicles at various developmental stages.Results: The current study showed significant differences of plasma E-cadherin levels (P = 0.003), primordial follicles count (P
Keywords: Ecadherin; rabbit ovary; ovarian reserve and folliculogenesis